(untitled) (European Journal of Pure and Applied Mathematics, 2025)
Pythagorean fuzzy digital fine b -door space (PFD bf -DS) is a novel notion of generalized Pythagorean fuzzy digital fine topological space that is presented in this paper. Additionally, a number of characterizations of Pythagorean fuzzy digital fine b -door space are examined. Examples were presented to demonstrate the applicability of these ideas and also some characteristics and connections between other Pythagorean fuzzy digital fine topological spaces and Pythagorean fuzzy digital fine b -door space were examined. Furthermore, an application which utilizes Pythagorean fuzzy digital fine topological space to select the best menstrual hygiene product for rural women is investigated.